Graft Compatibility of Local Grapevine Varieties with Grapevine Rootstocks in Yozgat Province - Selda Daler; Tuğba Kılıç; Harlene Hatterman-Valenti; Ozkan Kaya (Horticulturae, 2025)
Grafting compatibility between rootstocks and scions is a critical factor influencing the success of vine propagation and the long-term productivity of vineyards. This study aimed to evaluate the compatibility, sapling quality characteristics, and survival rates of grafted vines produced by combining ten local grape cultivars from Yozgat Province with four rootstocks: ‘5 BB’, ‘41 B’, ‘1103 P’, and ‘Fercal’. Grafted vines were assessed based on callus formation, graft union success, root development, and overall sapling quality. The results revealed that the ‘Fercal’ rootstock exhibited superior compatibility with several cultivars, notably achieving 100% graft success with ‘Siyah Üzüm’ and a high sapling rate of 93.4% with ‘Gelinparmağı’. Strong performance was also observed in the ‘Fercal/Köledoyuran’ and ‘Fercal/Horoz Üzümü’ combinations, which produced sapling rates of 95.4%. While ‘5 BB’ performed well with ‘Parmak Üzümü’ (100% graft success), ‘Karagevrek’ (94.4%), and ‘Mor Bulut’, it showed poor results with ‘Gelinparmağı’ (66.5% sapling rate). The ‘1103 P’ rootstock demonstrated good compatibility with ‘Şahmuratlı’ (94.3% graft success) and ‘Kirpi Üzümü’. In contrast, although ‘41 B’ reached up to 100% graft success in some combinations, it exhibited variable sapling development potential, ranging from 46.2% to 80.0%. Among the cultivars, ‘Siyah Üzüm’ achieved 100% compatibility with three rootstocks (‘41 B’, ‘1103 P’, and ‘Fercal’), followed by ‘Köledoyuran’, which consistently showed high success rates ranging from 96.9% to 100%. These findings offer practical guidance for selecting optimal rootstock–scion combinations to improve the efficiency of grafted vine production and reduce losses, particularly for local grape cultivars.